2005
DOI: 10.1614/wt-04-322r.1
|View full text |Cite
|
Sign up to set email alerts
|

Crop Tolerance and Weed Management Systems in Imidazolinone-Tolerant Corn (Zea mays L.)1

Abstract: Field studies were conducted in 1997 and 1998 to evaluate the efficacy of imidazolinone weed management systems and crop tolerance of imidazolinone-tolerant (IT) corn to imazapic. Imazapic (36 and 72 g/ha) was evaluated when applied PRE; early postemergence (EPOST), when corn was at the two- to three-leaf stage; and late postemergence (LPOST), when corn was at the six- to eight-leaf stage. Imazapyr + imazethapyr EPOST and metolachlor + atrazine followed by (fb) primisulfuron LPOST were evaluated as commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Imazapic at 0.04 to 0.07 kg/ha controlled greater than 90% smellmelon in corn regardless whether applied PRE, EPOST, or LPOST (Thompson et al, 2005). Grichar et al (2001) reported that imazapic provided consistent control ($ 85%) of citronmelon (Citrullus lanatus var.…”
Section: Smellmelon Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Imazapic at 0.04 to 0.07 kg/ha controlled greater than 90% smellmelon in corn regardless whether applied PRE, EPOST, or LPOST (Thompson et al, 2005). Grichar et al (2001) reported that imazapic provided consistent control ($ 85%) of citronmelon (Citrullus lanatus var.…”
Section: Smellmelon Controlmentioning
confidence: 99%
“…Smellmelon can be a problem at peanut harvest as the melon can become broken apart when run through the combine and increase drying time because of the high moisture content of the melon itself (author's personal observation). In IMI-tolerant corn (Zea mays L.), Thompson et al (2005) reported that imazapic at 0.07 and 0.14 kg ai/ha applied either preemergence (PRE), early POST, or late POST controlled smellmelon greater than 90%. Tingle and Chandler (2004) reported that smellmelon control was at least 93% with low-, medium-, and high-input herbicide systems.…”
mentioning
confidence: 99%
“…In previous studies, imazapic at 0.04 to 0.07 kg/ha controlled smellmelon greater than 90% in peanut or corn ( Zea mays L.) regardless whether applied PRE, EPOST, or LPOST (9,16). Grichar et al (8) reported that imazapic provided consistent control (≥ 85%) of citronmelon ( Citrullus lanatus var.…”
Section: Weed Controlmentioning
confidence: 94%
“…In 2013, using Induce with the low dose of imazapic did reduce C. melo control compared to the use of no adjuvant or ETA. Imazapic at 0.04-0.07 kg/ha controlled greater than 90% C. melo in corn (Zea mays L.) regardless whether applied either preemergence, early POST or late POST [42], while Grichar [43] has seen similar results in peanut with imazapic POST applications. The high humidities at application timing may have been a factor in the excellent control [44].…”
Section: Cucumis Melo L Controlmentioning
confidence: 98%